2011
DOI: 10.1111/j.1460-9568.2011.07883.x
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on the transcription factor Shox2 for specification of sensory neurons conveying discriminative touch

Abstract: Touch sensation is mediated by specific subtypes of sensory neurons which develop in a hierarchical process from common early progenitor neurons, but the molecular mechanism that underlies diversification of touch-sensitive mechanoreceptive neurons is not fully known. Here, we use genetically manipulated mice to examine whether the transcription factor short stature homeobox 2 (Shox2) participates in the acquisition of neuronal subtypes conveying touch sensation. We show that Shox2 encodes the development of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 41 publications
2
62
0
Order By: Relevance
“…Gene ontology (GO) analysis of annotated genes associated with Shox2 binding peaks indicated that Shox2 regulates genes that are associated with human phenotypes involving nervous system, bone and those that are linked to arrhythmia (Fig. 7A), consistent with the reported expression and function of Shox2 in the development of these organs (Abdo et al, 2011;Blaschke et al, 2007;Dougherty et al, 2013;Rosin et al, 2013;Vickerman et al, 2011;Yu et al, 2007). Interestingly, the GO analysis also revealed a direct association of Shox2 with cellular machineries responsible for active proliferation and transcription (supplementary material Fig.…”
Section: Shox2 Antagonizes Nkx2-5 Repression Of the Pacemaker Programsupporting
confidence: 67%
“…Gene ontology (GO) analysis of annotated genes associated with Shox2 binding peaks indicated that Shox2 regulates genes that are associated with human phenotypes involving nervous system, bone and those that are linked to arrhythmia (Fig. 7A), consistent with the reported expression and function of Shox2 in the development of these organs (Abdo et al, 2011;Blaschke et al, 2007;Dougherty et al, 2013;Rosin et al, 2013;Vickerman et al, 2011;Yu et al, 2007). Interestingly, the GO analysis also revealed a direct association of Shox2 with cellular machineries responsible for active proliferation and transcription (supplementary material Fig.…”
Section: Shox2 Antagonizes Nkx2-5 Repression Of the Pacemaker Programsupporting
confidence: 67%
“…Brn3a binds to a conserved upstream enhancer element within the Runx3 locus, suggesting that Runx factors repress TrkB expression downstream of Brn3a (Dykes et al 2010). It should be noted that separate studies suggest that the negative regulation of TrkB expression by Runx3 in sensory neurons mediating touch sensation is indirect and is mediated by another transcription factor, termed Shox2, which activates TrkB expression and is repressed by Runx3 (Abdo et al 2011).…”
Section: Runx1 Involvement In Establishment Of Cutaneous Sensory Circmentioning
confidence: 97%
“…Mechanoreceptive neurons (mechanoreceptors) also project their fibers to the spinal cord dorsal horn and the skin, but express other receptors for neurotrophic factors such as TrkB and TrkC. Proprioceptive neurons (proprioceptors) express TrkC and project to the ventral horn and intermediate zone of the spinal cord, as well as to muscle spindles and Golgi tendon organs (Inoue et al 2002;Kramer et al 2006;Yoshikawa et al 2007;Honma et al 2010;Abdo et al 2011;Lallemend and Ernfors, 2012). Both Runx1 and Runx3 are expressed in developing DRG sensory neurons, mostly in nonoverlapping patterns.…”
Section: Involvement Of Runx Genes In Peripheral Nervous System Develmentioning
confidence: 98%
“…Runx3 is expressed in TrkC+ proprioceptive neurons, promoting TrkC and suppressing Shox2 in these cells. 17,19 The molecular identity of signals controlling Ret, Shox2 and Runx3 expression in early-born sensory neurons is unclear, leaving it open how the diversification of mechanoreceptive and proprioceptive neurons is initiated. Similarly, little is known about the genes that execute the differentiation program of mechanoreceptive neurons.…”
Section: Molecular Mechanisms Of Mechanoreceptor Developmentmentioning
confidence: 99%
“…Consistent with this, Shox2 mutants have a deficit in a subset of mechanoreceptors that terminate in Meissner corpuscles and Merkel cells, and light touch sensation is strongly impaired. 17,18 Conversely, Runx3 blocks inappropriate gene expression programs in prospective proprioceptive neurons. Runx3 is expressed in TrkC+ proprioceptive neurons, promoting TrkC and suppressing Shox2 in these cells.…”
Section: Molecular Mechanisms Of Mechanoreceptor Developmentmentioning
confidence: 99%